Exploring media racial portrayal: awareness, sensitivity and implications / Zuliani Mohd Azni ... [et al.] - Mohd Azni, Zuliani; Hassan, Mohd Sufiean; Ibrahim, Noor Afzaliza Nazira; Sah Allam, Siti Nurshahidah; Abd Aziz, Siti Hajar; Khamis, Muhammad Hanapi; Yahaya, Fatimah Yazmin (Faculty of Information Management, 2023)
This study critically examines the intricate dynamics of media racial portrayal and its profound impact on individual perceptions and societal attitudes. With a focus on understanding the implications of heightened sensitivity to racial representation, the study delves into the ways in which media content can shape audience engagement and responses to racial biases and discrimination. Drawing on a comprehensive survey that gathered insights from a diverse range of participants, the study highlights key findings that underscore the prevalent awareness of racial portrayal in the media. Additionally, it emphasizes the substantial acknowledgment of the sensitivity surrounding media racial portrayal, suggesting a critical need to explore the multifaceted influence of this awareness on individual behaviors and societal attitudes. This paper employed a quantitative method of an online survey on Instagram and was utilized to collect the responses from 30 Malaysian young adults aged from 18 to 25 years old. The findings found that most of the respondents are against the idea of racism portrayed in the media and racism could be related to many types of crime such as cyberbullying, mockery, and slander that could lead to bickering in the mass media furthermore can form a negative sense in society.